ICC 2001. IEEE International Conference on Communications. Conference Record (Cat. No.01CH37240)
DOI: 10.1109/icc.2001.936986
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self-similarity on wireless data network performance

Abstract: -In this paper we investigate the impact of traffic patterns on wireless data networks. Modeling and simulation of the Cellular Digital Packet Data (CDPD) network of Telus Mobility (a commercial service provider) were performed using the OPNET tool. We use trace-driven simulations with genuine traffic trace collected from the CDPD network to evaluate the performance of CDPD protocol. This trace tends to exhibit longrange dependent behavior. Our simulation results indicate that genuine traffic traces, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Considering that future cellular networks will be able to carry IP traffic (particularly in indoor environments such as wireless LANs), it seems reasonable to have the same traffic characteristics for wired and wireless IP traffic. For example, Jiang et al [12] showed that cellular digital packet data traffic exhibits long-range dependencies. Finally, the reverse of signal to noise ratio defined as…”
Section: B Mmse Predictor Evaluationmentioning
confidence: 99%
“…Considering that future cellular networks will be able to carry IP traffic (particularly in indoor environments such as wireless LANs), it seems reasonable to have the same traffic characteristics for wired and wireless IP traffic. For example, Jiang et al [12] showed that cellular digital packet data traffic exhibits long-range dependencies. Finally, the reverse of signal to noise ratio defined as…”
Section: B Mmse Predictor Evaluationmentioning
confidence: 99%
“…It is also observed that the aggregated Internet traffic flows have similar patterns in different time scales, referred to as self-similarity [2]. Similarly, the existence of self-similarity in wireless network traffic flows has been observed [3] and has attracted attention in the research community [4]. The self-similarity characteristics result in that traffic engineering techniques, based on the traditional method, underestimate the required resources (such as transmission rate) to achieve quality-of-service (QoS) satisfaction.…”
Section: Introductionmentioning
confidence: 78%
“…With the increasing prevalence of high speed wireless systems capable of fast transmissions of large files (such as multimedia), there is a considerable literature analyzing wireless systems with heavy tails or long range dependence. Evidence of long range dependence and heavy tails in several wireless systems is reported in Kalden and Ibrahim (2004), Lee and Fapojuwo (2005), Jiang et al (2001), and others. In Teymori and Zhuang (2007), an ON-OFF source arrival with heavy-tailed ON periods is considered in studying queueing behavior.…”
Section: Introductionmentioning
confidence: 99%